PENGARUH MODEL KOOPERAIF TIPE CO-OP CO-OP TERHADAP KETERAMPILAN MEMAHAMI UNSUR-USUR INTRINSIK DALAM TEKS CERITA ANAK SISWA KELAS V SD NEGERI 56 PEKANBARU - Rudi Anto; Otang Kurniaman; Hendri Marhadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This research was based on by the lack of interaction between students and other students, that’s why the applied learning models cooperative type of Co-op Co-op to help students in developing the ability to interact and think. The purpose of this research was to know the effect of cooperative learning model Co-op Co-op against the skills to understand the intrinsic elements in the text of a children's story class V students of SD Negeri 56 Pekanbaru. This research is a quasi-experimental research with the research subjects were class V students at SDN 56 Pekanbaru, class VA as many as 29 students as an experimental class and class VB as many as 30 students as the control class. Results of research on first score after t test, students' initial ability tcount experimental class and control class meets the criteria -ttabel ≤ thitung ≤ ttable or -2,0025≤ 0.0021 ≤ 2.0025 This shows that Ho is accepted that there is no difference significant between experimental class students with control class on first tests. While the final score after t test, students' initial ability thitung experimental class and control class meets the criteria -ttabel ≤ thitung ≤ ttable or -2,00281 ≤ 0.0021 ≤ 2.0025 This shows that Ho is accepted that there is no difference significant between experimental class students with control class students on the final test. Based on the determination coefficient was 0.6934 with the effect as many as 48%, suggesting that the model cooperative of the type Co-op Co-op influencing skills to understand intrinsic elements of text children’s story with a high influence category. Based on the index gain, there are differences in the increase skill understanding the intrinsic elements wich significant between experimental class and control class. Increasing the skills to understand the intrinsic elements of students in the experimental class had an average increase (gain) is 0.42 with the medium category, while the control class is 0.10 with low category.Key Words: Cooperative Model Type Co-op Co-op, Skills Understanding IntrinsicElements